Remote sensing of suspended particulate matter concentrations in the Yellow River Estuary, China: algorithm development, long-term dynamics and driving mechanisms - Li, Peng; Chen, Shenliang; Ji, Hongyu; Zhong, Xiaojing; Qi, Jiarui; Gong, Xuelei; Yu, Peng; Ke, Yinghai (Frontiers in Marine Science, 2024)
Suspended particulate matter (SPM) concentrations and associated estuarine high turbidity zones (HTZ) play crucial role in maintaining delta land building, coastal wetlands and marine ecosystems. In the background of new water-sediment delivery regime and major geomorphological transition in delta, the long-term change characteristics and driving mechanisms of SPM and HTZ in the Yellow River Estuary (YRE) are not clarified. In this study, it was found that the existing SPM models could not be adapted to the extremely turbid YRE, for which a novel SPM retrieval algorithm and HTZ extraction method were developed. Spatiotemporal dynamics of SPM and HTZ in YRE from 1984 to 2023 were investigated using 798 Landsat TM/ETM+/OLI imageries. Results indicated that our proposed SPM algorithm outperformed all the previous models of YRE (R 2 > 0.95, relative percentage difference (RPD) < 22%), and high accuracies were achieved for both satellite-derived SPM (RPD = 33.01%) and HTZ (overall accuracy = 94%). Over the last four decades, both SPM concentration and HTZ distribution area in YRE had demonstrated an increasing and then decreasing trend, reaching a peak around 1996. HTZ experienced four morphological transformations involving the circular shape surrounding coast (1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993), the enlarged southeasterly ovoid shape (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007), the circle-like shape (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) and the thin northeasterly ovoid shape (2018)(2019)(2020)(2021)(2022)(2023). Riverine sediment load and strong-wind frequency controlled 67% of interannual SPM variability in the study area, and the former contributed more.Moreover, combination of weakening ocean dynamics and coastal erosion, coarsening of sediments, and coastal defense structures led to an exponential decline of SPM concentrations in northern subregion. High sediment discharge and rapid accretion of estuarine spit in 1984-1996 resulted in increased SPM concentrations in southern subregion and a quick expansion of HTZ into Laizhou Bay. With the geomorphological evolution of new and old estuaries, the high velocity zone and strong bottom shear stress zone were consequently adjusted, which explained the interannual variability of SPM and HTZ in the region. This study will contribute to understanding of the long-term evolutionary patterns of the coupled system consisting of runoff-tidal dynamics, sediment transport and geomorphological development in the estuary.